Peran Kepala Desa dalam Pengelolaan Aset Desa di Desa Pajaten Kecamatan Sidamulih Kabupaten Pangandaran - Nisa Izqi Naeli; Irfan Nursetiawan; Arie Budiawan (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
The problem phenomenon that occurs in managing village assets is due to the lack of role of the Village Government, so that due to these limitations existing village assets are unable to be optimized as a potential for increasing village income. The research objective to be achieved is to describe the role of the Village Government in implementing village asset management in Pajaten Village, Sidamulih District, Pangandaran Regency. This research is descriptive qualitative research, the data obtained is primary data and secondary data. Data collection techniques include structured interviews, participant observation and literature study. The results of this research are that the role of the Village Government in Managing Village Assets in Pajaten Village, Sidamulih District, Pangandaran Regency has not been implemented optimally. The obstacle faced is the limited understanding of the Village Government regarding its authority in making a policy product in managing village assets